Post-eruption species dynamic of Merapi National Park, Java, Indonesia - Suryanto, Priyono; Hamzah, Mohd. Zaki; Alias, Mohamad Azani; Mohamed, Azmy (Institute for Tropical Biology and Conservation, Universiti Malaysia Sabah, 2010)
A comprehensive study was carry out in Gunung Merapi National Park, Indonesia, to elucidate the species succession of the area within a three year period after the 2006 eruption. For this study, the selected area was divided into ive plots, namely P1, P2, P3, P4 and P5, each sized 50 x 20 m. Data collection was carried out for 18 months from May 2008, the close monitoring on species diversity, growth, recruitment, mortality and survival. Species diversity increased signiicantly (about 2 to 3 times) from census 1 in all the plots. The highest increase of richness was recorded in P5 (3.300±0.198 to 9.517±0.133), while the lowest was in P1 (1.907±0.458 to 3.824±0.841). Species heterogeneity within plots increased signiicantly. Similarly, evenness values in four plots, namely P1, P2, P3 and P4, increased signiicantly. There was an inverse-proportional pattern of relationship between the density and recruitment following the linear function of R2, which was about 0.029 to 0.438. The density and mortality were directly proportionate to the quadratic function of R2, which was about 0.807 to 0.936, with a p-value of <0.05. The initial result of this study can be used as basic reference for forest rehabilitation strategies on post eruption and supporting GMNP recreation especially the Merapi lava tour.